CADANGAN KARBON PADA TIGA MACAM PENGGUNAAN LAHAN DI DESA TUDUA KECAMATAN BUNGKU TENGAH KABUPATEN MOROWALI - Latae, Anas; Monde, Anthon; Hasanah, Uswah (AGROTEKBIS, 2019)
Climate change can be reduced by, among other things, suppressing the rate of soil carbon change, absorbing carbon and stored in the form of woody biomass, so the easiest way to increase carbon stocks is to maintain the integrity of natural forests and plant trees on agricultural lands to remain vegetated. This study aims to determine total soil organic matter, C-organic litter and grass on soil surface, species weight and carbon content of trees on three kinds of land use ie forest land, cocoa field and clove land in Tudua Village, Central Bungku District, Morowali District. Analysis of carbon stocks was carried out at the Soil Science Laboratory, Faculty of Agriculture, Tadulako University. This research was conducted in December 2016 until March 2017. The method used in this research is using quadrant method, which is one of the most common data retrieval method used in vegetation analysis. the results showed that the highest total soil organic matter found on forest land is 178,41 t ha-1and 108,76 t ha-1at a depth of 0-20 cm and 21-40 cm. Vegetation of trees on forest land is capable of producing the highest litter and grass with total dry weight 67,60 t ha-1so its carbon stock 31,09 t ha-1. The highest carbon content of tree vegetation is found in forest land 42,1490 t ha-1, while clove land amounts 36,215t ha-1and on a cocoa field of 8,9873 t ha-1.